Islamic Identity in the Digital Age: Between Firmness of Faith and the Challenges of Technology - Zainal Abidin Muhja; Liza Shahnaz (Yayasan Letiges Konsultan Sosial, 2025)
This study aims to explore the integration of technology and Islamic values ​​in the learning process and examine the paradigm of Islamic education in responding to the character crisis and digital identity disruption. The method used is library research with a qualitative approach. Data collection includes academic books, scientific journal articles, research reports, and other supporting documents. Data analysis techniques refer to the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing. Data validity techniques are carried out through source triangulation. The results of the study indicate that Islamic education offers a holistic solution by integrating the trilogy of tarbiyah-ta'lim-ta'dib, which rejects the dichotomy of religious knowledge and makes divine values ​​the foundation of the curriculum. Technology integration has been proven to dynamically strengthen Islamic identity through digital platforms, resulting in an 80% increase in learning motivation among Generation Z, while game-based learning increases literacy by 28%. Policy solutions include: empowering teachers as value filterers, synergy of content supervision (a collaborative role between parents), adoption of Islamic-based AI, and internalization of the tarbiyah-ta'lim-ta'dib trilogy in the national curriculum. The conclusion of this study confirms that the steadfastness of faith can be maintained through ethical technology integration and the reconstruction of responsive education policies. Islamic education can be a holistic solution to the digital era's character crisis by combining spiritual values, digital skills, and technological ethics. Thus, Islamic identity remains relevant and adaptive in the digital age. The originality of this study lies in the combination of social identity theory with the Islamic education paradigm to explain the formation of Islamic identity in the digital space. Due to limitations in secondary data and the lack of empirical field testing, further research using survey methods or case studies is needed to validate the findings